39. In-silico dosimetric evaluation of a new Linac MRI guided for pancreatic cancer SBRT treatment. (December 2018) - Cusumano, D.; Menna, S.; Boldrini, L.; Teodoli, S.; Placidi, E.; Chiloiro, G.; Placidi, L.; Greco, F.; Stimato, G.; Cellini, F.; Valentini, V.; De Spirito, M.; et al.
Abstract : Purpose: MR-guided adaptive Radiotherapy (MRgART) is considered a promising resource for pancreatic cancer, as it allows to online modify the dose distribution according to daily anatomy. This in silico study aims to compare the dosimetric performance of a 6 MV MR-Linac (MRIdian Linac, ViewRay) with those obtained using a standard 6 MV SBRT-Linac (Edge, Varian). Methods: Ten patients affected by locally advanced pancreatic cancer were considered. GTV, stomach, duodenum, liver, bowel bag, spinal cord and kidneys were contoured on the simulation CT scan and CTV was considered equal to GTV. PTV was generated from CTV adding an isotropic 3 mm margin and excluding areas of overlap with organ at risks (OARs). IMRT plans with 20 equidistant beams were performed for the MR-Linac, while dual arc VMAT plans were optimised for the SBRT-Linac. Prescription dose was 40 Gy in 5 fractions. All plans had to respect the following OARs constraints: V33Gy < 1 cc and V25Gy < 20 cc for duodenum, stomach and bowel bag, V12Gy < 50% volume for liver and kidneys, V25Gy < 0.5 cc for spinal cord[1] . The dosimetric comparison was performed on target coverage (D98CTV and V95PTV), dose homogeneity (HI), conformity index (CI) and dose diffusion (V10Gy, V20Gy). Statistical significance was estimated using the Wilcoxon-Mann-Whitney test for paired samples. Results: All results are summarised in Table 1 and Fig. 1: nine plans were considered clinically acceptable (V95PTV > 95%). Plans calculated with standard Linac show less low dose diffusion and higher CTV homogeneity, probably due to the different optimisation software, that is more sophisticated but also slower in processing (optimisation mean time ̃25 min) in comparison to the MR-Linac one (∼2 min). Conclusions: Dosimetric performance between MR and standard Linac is comparable in SBRT pancreatic treatment. Considering the MRgART need to optimise the treatment plan while the patient is on the couch, MR Linac allows to elaborate clinically and dosimetrically satisfying SBRT plans for pancreatic cancer.